Contactless conductivity detection for analytical techniques: Developments from 2016 to 2018. Issue 1 (2nd August 2018) - Kubáň, Pavel; Hauser, Peter C.
Abstract: The publications concerning capacitively coupled contactless conductivity detection for the 2‐year period from mid‐2016 to mid‐2018 are covered in this update to the earlier reviews of the series. Relatively few reports on fundamental investigations or new designs have appeared in the literature in this time interval, but the development of new applications with the detection method has continued strongly. Most often, contactless conductivity measurements have been employed for the detection of inorganic or small organic ions in conventional capillary electrophoresis, less often in microchip electrophoresis. A number of other uses, such as detection in chromatography or the gauging of bubbles in streams have also been reported.